1993
DOI: 10.1093/cvr/27.2.334
|View full text |Cite
|
Sign up to set email alerts
|

Role of locally formed angiotensin II and bradykinin in the reduction of myocardial infarct size in dogs

Abstract: Angiotensin II is locally produced in the ischaemic heart by both serine protease(s) and chymostatin inhibitable protease(s), but not by angiotensin converting enzyme. From the reduction in myocardial infarct size produced by angiotensin converting enzyme inhibition, it seems that bradykinin accumulation may play a more important role than the suppression of angiotensin II formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(45 citation statements)
references
References 0 publications
1
44
0
Order By: Relevance
“…26 Increases in Ang II levels from the anterior interventricular vein during ischemia were suppressed by the serine protease inhibitors nafamostat and chymostatin and were unaffected by captopril. In addition, we have previously shown that chronic mitral regurgitation in the dog results in an increase in cardiac mast cells, which correlates positively with the increase in cardiac chymase activity.…”
Section: Discussionmentioning
confidence: 97%
“…26 Increases in Ang II levels from the anterior interventricular vein during ischemia were suppressed by the serine protease inhibitors nafamostat and chymostatin and were unaffected by captopril. In addition, we have previously shown that chronic mitral regurgitation in the dog results in an increase in cardiac mast cells, which correlates positively with the increase in cardiac chymase activity.…”
Section: Discussionmentioning
confidence: 97%
“…Twentythree patients were treated with streptokinase (1.5 million IU IV over 60 minutes) and 18 were treated with rTPA (8 with bolus of 10 mg IV, followed by 50 mg infused over 60 minutes and then 40 mg infused over 120 minutes; 10 patients were administered rTPA and heparin according to the accelerated infusion protocol indicated by the GUSTO study). C4a and C3a were measured by radioimmunoassay, soluble terminal complement components (SC5b-9) and anti-SK IgG antibodies were measured by ELISA.…”
mentioning
confidence: 99%
“…In the present study, there was no evidence for AT1 receptor activation by endogenously formed angiotensin II during normoxic incubation, as demonstrated by unchanged noradrenaline release after antagonism of the AT1 receptor. This is well explained by a negligible formation of angiotensin II in the heart during normoxic conditions (Noda et al, 1993). In anoxia, however, the AT1 receptor was maximally stimulated by endogenous angiotensin II, as documented by an attenuation of noradrenaline release by losartan alone and the lack of effect of exogenous angiotensin II in anoxia.…”
Section: Facilitatory Receptorsmentioning
confidence: 79%
“…A reason for this finding could be a maximal activation of these receptors by endogenous transmitters during anoxia. In fact, a substantial increase of angiotensin II formation during ischaemia has been reported (Noda et al, 1993). The increase of local angiotensin II concentrations at the receptor site may lead to maximal activation of the presynaptic AT1 receptor by endogenous angiotensin II in anoxia.…”
Section: Facilitatory Receptorsmentioning
confidence: 99%